WhaleRank: an optimisation based ranking approach for software requirements prioritisation. (2018) - Anand, R. Vijay; Dinakaran, M.
Requirement prioritisation is one of the major areas in the software product development process. Ranking methods employed for prioritising orders the requirements based on their importance. Ranking the requirements contributes in enhancing the quality of the product using additional features and to attain customer satisfaction. However, effectiveness is the growing concern in requirement prioritisation. This paper proposes a ranking method WhaleRank to rank the requirement and the effectiveness of ranking gets enhanced using the whale optimisation algorithm (WOA). The WhaleRank method uses four ranking functions based on dictionary words, similarity measure, perception of the manager, and the newly updated requirements that are combined to form a linear rank using the ranking constants. WOA determines the optimal weights of the ranking constants that promote to determine the optimal rank for the requirements. Experimentation with the methods like CBRank, average rank, WhaleRank, and GA provide a comparative performance analysis that proves that the proposed WhaleRank outperforms all methods in terms of accuracy and disagreement measure (NDA) and the values of accuracy and NDA is 83.33% and 16.24% respectively.